Three new earthworms of the genus Pheretima (Oligochaeta: Megascolecidae) from Mt. Makiling, Luzon Island, Philippines - Hong, Yong; James, Samuel W. (Zootaxa, 2008)
Earthworm material collected from Mt. Makiling, Laguna Province, Philippines contained three new species of the genus Pheretima as defined by Sims and Easton (1972): Pheretima makilingensis sp. nov. in the P. urceolata group, characterized by spermathecal pores in 5/6; Pheretima mariae sp. nov. and Pheretima lagunaensis sp. nov. in the P. sangirensis group, having spermathecal pores in 7/8. Pheretima makilingensis sp. nov. has spermathecal pores 0.15 circumference ventrally apart and male openings 0.17 circumference ventrally apart. Pheretima mariae sp. nov. has spermathecal pores 0.04 circumference ventrally apart, male openings 0.09 circumference ventrally apart, copulatory bursae without pads, and a large digitate penis filling bursa. Pheretima lagunaensis sp. nov. has spermathecal pores 0.03 circumference ventrally apart, male openings 0.10 circumference ventrally apart, copulatory bursae lacking pads, and a large irregularly shaped penis from the bursa roof.